EP376 BRCA1 immunohistochemistry expression and survival in cervical cancer. (1st November 2019) - Paik, ES; Lee, JH; Kang, M; Kang, JH; Jeong, SY; Kim, MS; Lee, Y-Y; Kim, T-J; Lee, J-W; Kim, B-G; Bae, D-S; Seo, J; et al.
Abstract : Introduction/Background: BRCA1 expression can be lost by a variety of mechanisms including germline or somatic mutation and promotor hypermethylation. Given the potential importance of BRCA1 loss as a predictive and prognostic biomarker in several cancers, we investigated immunohistochemistry (IHC) of BRCA1 in cervical cancer and their possible prognostic relevance. Methodology: Seventy patients with cervical cancer were enrolled in this study. Samples from each tumor were stained for BRCA1 and reviewed independently by gynecologic pathologists blinded to BRCA status. Kaplan-Meier methods were used to estimate overall survival (OS), and the log-rank test was used to assess differences between groups. Gene lists obtained from microarray analysis were analyzed for Gene Ontology enrichment using DAVID tools. Results: BRCA1 IHC was positive in 62.9% (44/70) of cases. IHC staining confirmed expression of BRCA1 in patients with better OS (p=0.028). Genomic profiling of the tumors showed specific alterations associated to BRCA1 expression in the tumors, affecting relevant cellular processes. Alteration of SNORD8, PGK1, CCR6 and COL1A2 gene signatures was identified to be associated with survival outcomes of patients. Conclusion: These results support the fact that BRCA1 IHC expression in cervical cancer is associated with survival. In addition, the identification of specific alterations in cervical cancer associated with BRCA1 protein expression would help to provide individualized prediction in these patients. Disclosure: Nothing to disclose.